Associations between the physiological basis of fabric-evoked prickle, fiber and yarn characteristics and the Wool ComfortMeter value. Issue 11 (July 2015) - Naebe, Maryam; McGregor, Bruce A; Swan, Paul; Tester, David
The association between the incidents counted by the measurement wire of the Wool ComfortMeter (WCM) and the previously published neurophysiological basis for fabric-evoked prickle have been investigated for lightweight knitted woolen fabrics. The fiber lengths and diameters capable of triggering the fabric-evoked prickle sensation were calculated using Euler's buckling formula, and it is suggested that fibers as fine as 10 µm are capable of triggering the prickle response if they have a short enough free length protruding from the surface. Good agreement was found between the sensory assessed human prickle sensation and the wearer prickle response predicted using the WCM outputs, especially when the latter were transformed using Stevens's Psychophysical Power Law.